THE TRADITION OF RESPONDING TO THE QUR'AN (Ethnography Studies: Systematic and Cultural Analysis) - M.Ikhsan Nawawi; Nazwa Momen Omar (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2022)
This paper aims to show the extent to which a memorization system is still needed in maintaining the purity of the Qur'an by looking for a point of accuracy having a system that is used to maintain authentication of various forms or symbols embedded through writing (writing) or in the form of sound that is recorded for integrity. , the purity of the verses of the Koran. Although its usefulness has been widely used in the needs of the study of the Qur'an. Armed with an ethnographic (study) method, the orientation towards the tradition ofmemorizing the Koran in research is divided into three types, as pure worship, as maintenance of the authenticity of the Koran, and examples of studies in Islamic education. Through ethnography studies (research methods) as a systematic description and analysis of the culture of a group, people or ethnic group collected from the field in the same period. The system and process of recording revelations (jam al-qur'an) can then be classified into two words used, namely jam al-qur'an, which is memorizing and writing the Koran.Hammalah al-qur'an in the sense of rote, such as recording the memorized al-qur'an from being destroyed by remembering (saving) in the heart or mind (memory). As for the term jam' al-Qur'an, the meaning of writing in the form of verses of the Qur'an is written as a result of revelation that is revealed in verbal form. Until the time the activities of memorizing and writing the Qur'an continue to be more established. In countries inhabited by Muslims in various parts of the world, finding centers of Islamic learning uses the primary activity of memorizing the Qur'an. when the protection of the memorized Qur'an is no longer played as a method or stage of understanding, but rather as a scientific model, as a goal. On the other hand, there are some Muslims who interpret the text of the Qur'an by studying and deepening it critically.